Service quality, customer satisfaction and loyalty: a case study in Vietnamese SMEs - Nga Phan Thi Hang; Nguyen Kim Quoc Trung (Cogent Business & Management, 2024)
This study assesses how various aspects of loan service quality in Vietnamese commercial banks impact the satisfaction levels of small and medium enterprises (SMEs) and their relationship with customer loyalty to these banks. Implementing both qualitative methods (such as group discussions, expert interviews, and customer surveys) and quantitative methods (including partial least squares structural equation modeling (PLS-SEM)), the authors identified and analyzed five dimensions of loan service quality—tangibility, reliability, assurance, responsiveness, and empathy—that positively influence SME satisfaction within these banks. Additionally, this study explores the connection between SME satisfaction and loyalty, recognizing it as a crucial factor for improving operational efficiency and gaining a competitive advantage in facilitating banking transactions.
Keywords: 650; Service quality; loans; customer loyalty; customer satisfaction; small and medium enterprises